1990
DOI: 10.1002/chin.199033188
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Structural Requirements for Agonist Actions at the Benzodiazepine Receptor: Studies with Analogues of 6‐(Benzyloxy)‐4‐(methoxymethyl)‐β‐carboline‐3‐carboxylic Acid Ethyl Ester.

Abstract: Starting with the title compound (I), the β‐carboline derivatives (II) and (IV) are prepared by known procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…In addition, the indolo[3,2-b]isoquinoline 13 has been recently prepared and shown to be inactive (IC50 » 2 µ ) at BzR.10 As reported,3 the diindole 14 exhibits an IC50 of 4 nM, but simple deletion of the N( 7)-H function has completely eliminated the affinity of this diindole to provide the inactive indolo[3,2-6]isoquinoline.10…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the indolo[3,2-b]isoquinoline 13 has been recently prepared and shown to be inactive (IC50 » 2 µ ) at BzR.10 As reported,3 the diindole 14 exhibits an IC50 of 4 nM, but simple deletion of the N( 7)-H function has completely eliminated the affinity of this diindole to provide the inactive indolo[3,2-6]isoquinoline.10…”
Section: Resultsmentioning
confidence: 96%
“…This suggests that the keto rather than the proposed enol form is the bioactive form. 4 In the keto form, the quinoline 11 is able to interact at both hydrogen bonding interaction sites A2, Hx of the pharmacophore,3,6 whereas the enol tautomer cannot interact at either site, regardless of the direction of approach of the ligand to the binding site.…”
Section: Resultsmentioning
confidence: 99%
“…ZK 91085 was tested for an anticonvulsant action in mice ( Hollinshead et al ., 1990 ). This β‐carboline displayed no effect at 40 mg kg −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of a ligand with both A 2 and H 1 sites of the BZ-binding domain of the receptor (Fig. 5) appears obligatory for inverse agonist activity (39,40). It has also been reported that smaller lipophilic substituents at position 3, which lie close to the plane of the β-carboline ring system, tend to yield inverse agonists, while analogs carrying longer or bulkier substituents at the same position possess antagonist activity (38).…”
Section: B-carbolinesmentioning
confidence: 91%
“…CNS Drug Reviews, Vol. 5 With respect to substitutions at position 6 of β-carboline (38,39) the benzyl oxygen and benzylamino nitrogen have been closely correlated to the potency of the compound via a recent study which employed a series of 6-benzyloxy and 6-benzylamino analogs to study such effects. Additionally, the phenyl ring of the β-carboline has been shown to play an important role in its hydrophobicity.…”
Section: B-carbolinesmentioning
confidence: 99%